Respuesta :

2x + 2y = 16 ⇒ 2x + 2y = 16
3x -  1y =   4 ⇒ 6x -  2y =   8
                                 8x = 24
                                  8      8
                                   x = 3
                         2x + 2y = 16
                       2(3) + 2y = 16
                           6 + 2y = 16
                         - 6           - 6
                                 2y = 10
                                  2      2
                                   y = 5
                             (x, y) = (3, 5)
The systems of equations that has the same solution as the system is one common solution.